Teknik Sipil Menyenangkan: Membangun Generasi Penerus Cerdas dengan Pengenalan Teknik Sipil - Iqbal; Rajib Muammar; Yuslinda; Muttaqin (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2024)
This community service program aims to introduce civil engineering to students of SMK Negeri 2 Karang Baru, Aceh Tamiang, in order to build a smart and competent future generation in the field of construction. Through enjoyable and practical learning methods, students are introduced to the basics of structural design, building techniques, and the use of modern technology in construction. The program results show a significant increase in students' knowledge and skills, as well as increased interest in careers in civil engineering. This program has also succeeded in boosting students' confidence in applying civil engineering concepts. This success provides a strong foundation for further development and replication of the program in other schools. Keywords: Civil Engineering, Enjoyable Learning, Structural Design, Building Techniques, Construction Technology